2014
DOI: 10.1093/ntr/ntu148
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Ever Having Used Electronic Cigarettes Among Older Adolescent Children of Alcoholic Fathers

Abstract: introduction:Few studies have examined predictors of ever having used electronic cigarettes (or e-cigarettes) among older adolescents. This study examined correlates of ever having used e-cigarettes among adolescent children of alcoholic fathers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
1
14
0
2
Order By: Relevance
“…323,333,336339,342,344,346,348,350,351,354357,359,361,369,380,381,384,395,396,421,455,461,472,504,527,531,541,543,551,552,561,568,575,577579,582,584,590 National Health Interview Survey data show that recent former smokers (quit <1 year ago) were more likely to report using ENDS “every day” or “some days” (22.0%) than adults who had never smoked (0.4%), former smokers who had quit for ≥1 year (2.3%), or former smokers who quit cigarettes ≥4 years ago (0.8%). 610,639 Studies show the use of ENDS is correlated with use of other tobacco products, 325,362,394,468,509,517,520,524,557,558,584,585,621,649 marijuana, 325,432,496,512,523,539,559,571,592,593,609,642 and alcohol. 325,432,496,497,512,523,539,549,559,563,571,572,584,590,592,593,609,650 …”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…323,333,336339,342,344,346,348,350,351,354357,359,361,369,380,381,384,395,396,421,455,461,472,504,527,531,541,543,551,552,561,568,575,577579,582,584,590 National Health Interview Survey data show that recent former smokers (quit <1 year ago) were more likely to report using ENDS “every day” or “some days” (22.0%) than adults who had never smoked (0.4%), former smokers who had quit for ≥1 year (2.3%), or former smokers who quit cigarettes ≥4 years ago (0.8%). 610,639 Studies show the use of ENDS is correlated with use of other tobacco products, 325,362,394,468,509,517,520,524,557,558,584,585,621,649 marijuana, 325,432,496,512,523,539,559,571,592,593,609,642 and alcohol. 325,432,496,497,512,523,539,549,559,563,571,572,584,590,592,593,609,650 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…610,639 Studies show the use of ENDS is correlated with use of other tobacco products, 325,362,394,468,509,517,520,524,557,558,584,585,621,649 marijuana, 325,432,496,512,523,539,559,571,592,593,609,642 and alcohol. 325,432,496,497,512,523,539,549,559,563,571,572,584,590,592,593,609,650 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…Although counterintuitive (e.g., Lessard et al, 2014), this finding is suggestive that, owing to their rather modest emission effect compared to conventional cigarettes (Callahan-Lyon, 2014), adolescent e-cigarette use may go easier unnoticed by parents.…”
Section: Discussionmentioning
confidence: 95%
“…15 A recent survey of more than 15 000 US adolescents in grades 6 through 12 found that e-cigarette use was significantly lower in girls and in African American and Hispanic youth and higher for those who smoked conventional cigarettes or who had friends who smoked. 16 Among older adolescent children of alcoholic fathers, Lessard and colleagues 17 reported that e-cigarette use was associated with current use of cigarettes, alcohol, and marijuana. In another study, 18 adolescent users of e-cigarettes were found to be just as likely as tobacco users to report the use of alcohol, cigars, smokeless tobacco, and marijuana but were more likely to report the use of blunt wraps and hookahs.…”
Section: User Demographicsmentioning
confidence: 99%